The Synergistic Larvicidal Activities of Three Local Plants on Aedes Aegypti (Global Journal of Science Frontier Research, 2016)
The synergistic activity of extracts of Lantana camara, Stachytarpheta indica and Allamanda blanchetii against Aedes aegypti mosquito larvae were investigated. Ethanolic leaf extracts of these plants were tested separately and combined on Ae. aegypti larvae with concentration ranging from 5, 10, 20, 30 and 40mg/ml. In 72 hours bioassay experiment, mortalities were observed at the different time intervals but were highest at 40mg/ml concentration for the three plants independently, with the L. camara extract showing better larvicidal activity over the other plant extracts at 48 hours and 72 hours exposure. The LC 50 of L. camara (6.08mg/ml), S. indica (8.15mg/ml) and A. blanchetii (6.44g/ml) indicates their ability to cause 50% larval mortality at such low concentrations. For the synergistic effects, all the concentrations exhibited high mortality at 48 hours and 72 hours exposure. The 40mg/ml showed the highest larvicidal activity (100% mortality) after 48 hours exposure with the L2:A1:S1 combination. Synergistic factor (S.F.) of 1.00, 1.27 and 0.94 were obtained for L. camara, S. indica and A. blanchetii. Synergism was recorded for L. camara and S. indica, while antagonism was recorded for A. blanchetii.
Keywords: extracts; ethanol; synergism; mosquito; control; aedes